SELF-REPORTED ADVERSE EFFECTS OF MONO- AND POLYTHERAPY FOR EPILEPSY. (29th November 2012) - Wieshmann, U; Andrew, T; Milinis, K; Baker, G
Abstract : Polytherapy is increasingly common because of the large number of new Anti Epileptic Drugs (AED). We carried out a study to determine if polytherapy has more adverse effects (AE) than monotherapy. Methods: We compared three groups: monotherapy (n=186), polytherapy (n=325) and control subjects no taking AED (n=65). We used the Liverpool Adverse Event Profile (LAEP) to ascertain AE and to calculate the total AE score. We also recorded the frequency of refractory epilepsy, depression subscores on the LAEP and drug doses. Results: The mean LAEP scores were significantly higher in polytherapy (45.56, CI=44.36 to 46.76) than in monotherapy (42.29, CI=40.65 to 44.02) and controls (33.25, CI=31.05 to 35.44). Tiredness, memory problems and difficulty concentrating were the most common symptoms in patients taking AED. The frequencies of symptoms reported as always or sometimes a problem were as follows: tiredness (polytherapy/monotherapy/controls) 82.5%/75.6%/64.6%, memory problems 76%/63.2%/29.2% and difficulty concentrating 68%/63.9%/30.8%. The proportion of seizure free patients was significantly lower in the polytherapy group (17%) than in the monotherapy group (55%). Depression rates between the monotherapy and polytherapy groups were similar. Drug dosages were higher in polytherapy, however this was not statistically significant. Conclusion: Patients on polytherapy had significantly higher LAEP scores than patients on monotherapy. This should be carefully discussed with the patient before a second AED is added.